Watersheds and mining tailings - Ángel Canales-Gutiérrez (Journal of the Selva Andina Biosphere)
and drinking water activities. However, the growing formal and informal mining activity causes environmental impacts on aquatic and terrestrial ecosystems, affecting the health of families living in the area of influence.